HIGH-CHROMIUM SPINELLIDS AS SOURCES OF INFORMATION ON THE ORIGIN OF BASALT MAGMA - Poroshin Y.Y. (My University, 1987)
A description is given of the compositions of high-chromium spinellid varieties from the Ural and Altai-Sayan basalts. These spinellids belong to the following rock associations: trachybasalt (tb), trachybasalt-trachyandesite (tbta), sodic basalt (sb), sodic basalt-rhyolite (sbr), basalt-andesite-rhyolite (bar), andesite-basalt (ab) and basalt-andesite (ba). Based on their analysis, the authors conclude that the 'geosynclinal' basalts and the ultramafic rocks of dunite-peridotite and dunite-clinopyroxenite-gabbro associations, accompanying them in the same structural facies zones, were derived from the same mantle substrate. The basalt magma separated from a mantle substrate which was equivalent in composition to dunite, and whose restite minerals included the chrome spinellids investigated by us.